Analysis of Language Errors Syntactic Review for the Tarkîb Washfî Category in the Student Thesis - Tulus Musthofa; Nafisatun Nisa; Abd Rauf Hassan (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
This study aims to discover the mistakes in understanding and using Arabic grammatical rules, especially in the syntactic review of the as-shîfah wa al-maushûf category in the Arabic education student thesis (PBA). The research object is only limited to the discussion chapter, which results from the author's ideas and expressions as outlined in Arabic writing. This type of research is descriptive qualitative research with content analysis, which aims to examine, describe and evaluate the language errors of S1 PBA students at Sunan Kalijaga State Islamic University for 2020-2021. The results show that the most errors at the as-shîfah wa al-maushûf occur in the mudzakkar wa mu'annats rule than the rule nakirah wa ma'rifah. Factors that cause errors occur due to a lack of mastery of language and writing rules and the absence of intensive writing practice. The solution offered is to train to write intensively and explore the knowledge needed to support the writing skills (mahârah al-kitâbah).